Photon avalanching nanoparticles inducing giant nonlinear optical responses and method for providing or fcilitating giant nonlinear optical responses from photon avalanching nanoparticles

KR103032010B1Active Publication Date: 2026-10-13KOREA RES INST OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020220005556
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2026-10-13
Estimated Expiration
2042-01-13

Smart Images

  • Figure 112022004881414-PAT00066_ABST
    Figure 112022004881414-PAT00066_ABST
Patent Text Reader

Abstract

A nanoparticle according to one embodiment for inducing photon avalanching may comprise a nanocrystal doped with at least 5 at% thulium (Tm), and the nanoparticle may comprise only thulium. The atomic concentration of thulium may be at least 8%. The near-infrared excitation wavelength of the nanocrystal may be 1064 nm or greater, and the near-infrared excitation wavelength may be 1400 nm to 1490 nm. The nanocrystal may further comprise an inert shell that can surround the nanocrystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to avalanche nanoparticles that cause large nonlinear optical phenomena, and more specifically, to a method for causing or promoting large nonlinear optical phenomena from avalanche nanoparticles. Background Technology

[0002] One of the various advantages of utilizing the photon avalanche (PA) phenomenon, in which a material emits a disproportionately large number of photons when emitting light above a critical intensity, is a combination of extreme nonlinearity and efficiency that can be achieved without periodic structuring or interference effects.

[0003] PA was critical pump laser intensity (I) about 40 years ago P Pr exhibiting a rapid increase in upconverted luminescence when excited above ) 3+ It was first observed in ion-doped bulk crystals (Ref. 3). This discovery led to the development of bulk PA materials based on other lanthanide rare earth elements, utilized, for example, in efficient upconversion lasers (Ref. 4-6 and 16), and their unique properties continue to attract interest across various fields (Ref. 6 and 7).

[0004] However, there is a need to derive a method to induce or promote large-scale nonlinear optical phenomena from avalanche nanoparticles in order to overcome the shortcomings shown in the aforementioned references, such as, for example, avalanche efficiency. Prior art literature

[0005] The following references are hereby incorporated by reference, in their entireties:1. Turcotte, D. L. Self-organized criticality. Rep. Prog. Phys. 62, 1377-1429 (1999).2. Ni, H. & Rand, S. C. Avalanche phase conjugation. Opt. Lett. 17, 1222-1224 (1992).3. Chivian, J. S., Case, W. E. & Eden, D. D. The photon avalanche: A new phenomenon in Pr3+ -based infrared quantum counters. Appl. Phys. Lett. 35, 124-125 (1979).4. Lenth, W. & Macfarlane, R. M. Excitation mechanisms for upconversion lasers. J. Lumin. 45, 346-350 (1990).5. Joubert, M.-F. Photon avalanche upconversion in rare earth laser materials. Optical Materials 11, 181-203 (1999).6. Auzel, F. Upconversion and Anti-Stokes Processes with f and d Ions in Solids. Chemical Reviews 104, 139-174 (2004).7. Bednarkiewicz, A., Chan, E. M., Kotulska, A., Marciniak, L. & Prorok, K. Photon avalanche in lanthanide doped nanoparticles for biomedical applications: super-resolution imaging. Nanoscale Horizons 4, 881-889 (2019).8. Thompson, M. A., Lew, M. D. & Moerner, W. E. Extending Microscopic Resolution with Single-Molecule Imaging and Active Control. Annual Review of Biophysics 41, 321-342 (2012).9. Gustafsson, M. G. L. Nonlinear structured-illumination microscopy: Wide-field fluorescence imaging with theoretically unlimited resolution. Proceedings of the National Academy of Sciences of the United States of America 102, 13081 (2005).10. Heintzmann, R. & Huser, T. Super-Resolution Structured Illumination Microscopy. Chemical Reviews 117, 13890-13908 (2017).11. Denkova, D., Ploschner, M., Das, M., Parker, L. M., Zheng, X., Lu, Y., Orth, A., Packer, N. H. & Piper, J. A. 3D sub-diffraction imaging in a conventional confocal configuration by exploiting super-linear emitters. Nat. Commun. 10, 3695 (2019).12. Liu, Y., Wang, F., Lu, H., Fang, G., Wen, S., Chen, C., Shan, X., Xu, X., Zhang, L., Stenzel, M. & Jin, D. Super-Resolution Mapping of Single Nanoparticles inside Tumor Spheroids. Small 16, 1905572 (2020).13. Marciniak, L., Bednarkiewicz, A. & Elzbieciak, K. NIR-NIR photon avalanche based luminescent thermometry with Nd3+ doped nanoparticles. Journal of Materials Chemistry C 6, 7568-7575 (2018).14. Pickel, A. D., Teitelboim, A., Chan, E. M., Borys, N. J., Schuck, P. J. & Dames, C. Apparent self-heating of individual upconverting nanoparticle thermometers. Nat. Commun. 9, 4907 (2018).15. Lay, A., Sheppard, O. H., Siefe, C., McLellan, C. A., Mehlenbacher, R. D., Fischer, S., Goodman, M. B. & Dionne, J. A. Optically Robust and Biocompatible Mechanosensitive Upconverting Nanoparticles. ACS Central Science 5, 1211-1222 (2019).16. Xie, P. & Gosnell, T. R. Room-temperature upconversion fiber laser tunable in the red, orange, green, and blue spectral regions. Opt. Lett. 20, 1014-1016 (1995).17. Guy, S., Joubert, M. F. & Jacquier, B. Photon avalanche and the mean-field approximation. Phys. Rev. B 55, 8240-8248 (1997).18. Deng, H., Yang, S., Xiao, S., Gong, H.-M. & Wang, Q.-Q.Controlled Synthesis and Upconverted Avalanche Luminescence of Cerium(III) and Neodymium(III) Orthovanadate Nanocrystals with High Uniformity of Size and Shape. Journal of the American Chemical Society 130, 2032-2040 (2008).19. Wang, Q.-Q., Han, J.-B., Guo, D.-L., Xiao, S., Han, Y.-B., Gong, H.-M. & Zou, X.-W. Highly Efficient Avalanche Multiphoton Luminescence from Coupled Au Nanowires in the Visible Region. Nano Lett. 7, 723-728 (2007).20. Ma, Z., Yu, Y., Shen, S., Dai, H., Yao, L., Han, Y., Wang, X., Han, J.-B. & Li, L. Origin of the Avalanche-Like Photoluminescence from Metallic Nanowires. Scientific Reports 6, 18857 (2016).21. Liu, Y., Lu, Y., Yang, X., Zheng, X., Wen, S., Wang, F., Vidal, X., Zhao, J., Liu, D., Zhou, Z., Ma, C., Zhou, J., Piper, J. A., Xi, P. & Jin, D. Amplified stimulated emission in upconversion nanoparticles for super-resolution nanoscopy. Nature 543, 229-233 (2017).22. Levy, E. S., Tajon, C. A., Bischof, T. S., Iafrati, J., Fernandez-Bravo, A., Garfield, D.J., Chamanzar, M., Maharbiz, M. M., Sohal, V. S., Schuck, P. J., Cohen, B. E. & Chan, E. M. Energy-Looping Nanoparticles: Harnessing Excited-State Absorption for Deep-Tissue Imaging. ACS Nano 10, 8423-8433 (2016).23. Fernandez-Bravo, A., Yao, K., Barnard, E. S., Borys, N. J., Levy, E. S., Tian, B., Tajon, C. A., Moretti, L., Altoe, M. V., Aloni, S., Beketayev, K., Scotognella, F., Cohen, B. E., Chan, E. M. & Schuck, P. J. Continuous-wave upconverting nanoparticle microlasers. Nat. Nanotechnol. 13, 572-577 (2018).24. Si, X., Li, Z., Qu-Quan, W., Hong, D. & Shi-He, Y. Energy Transfer and Avalanche Upconversion of Nd x Y 1- x VO 4 Nanocrystals. Chin. Phys. Lett. 26, 124209 (2009).25. Bednarkiewicz, A. & Strek, W. Laser-induced hot emission in Nd3 / Yb3 : YAG nanocrystallite ceramics. J. Phys. D: Appl. Phys. 35, 2503-2507 (2002).26. Dwivedi, Y., Bahadur, A. & Rai, S. B. Optical avalanche in Ho:Yb:Gd2O3 nanocrystals. J. Appl. Phys. 110, 043103 (2011).27. Wang, G., Peng, Q. & Li, Y.Luminescence Tuning of Upconversion Nanocrystals. Chemistry - A European Journal 16, 4923-4931 (2010).28. Zhou , B. , Shi , B. , Jin , D. & Liu , X. Controlling upconversion nanocrystals for emerging applications . Nat. Nanotechnol. 10, 924–936 (2015).29. Tian , B. , Fernandez-Bravo , A. , Najafiaghdam , H. , Torquato , NA , Altoe , MVP , Teitelboim , A. , Tajon , CA , Tian , Y. , Borys , NJ , Barnard , ES , Anwar , M. , Chan , EM , Schuck , PJ & Cohen , BE Low irradiance multiphoton imaging with alloyed lanthanide nanocrystals. Nat. Commun. Rev. 9, 3082 (2018). Tajon , CA , Yang , H. , Tian , B. , Tian , Y. , Ercius , P. , Schuck , PJ , Chan , EM & Cohen , BE Photostable and efficient upconverting nanocrystal-based chemical sensors . Optical Materials 84, 345–353 (2018).31. Buenzli , J.-CG & Piguet , C. Taking Advantage of Luminescent Lanthanide Ions . Chem. Soc. Rev. Fr. 34, 1048–1077 (2005).32. Gnach , A. , Lipinski , T. , Bednarkiewicz , A. , Rybka , J. & Capobianco , JAUpconverting nanoparticles: assessing the toxicity. Chem. Soc. Rev. 44, 1561-1584 (2015).33. Gargas, D. J., Chan, E. M., Ostrowski, A. D., Aloni, S., Altoe, M. V. P., Barnard, E. S., Sanii, B., Urban, J. J., Milliron, D. J., Cohen, B. E. & Schuck, P. J. Engineering bright sub-10-nm upconverting nanocrystals for single-molecule imaging. Nat. Nanotechnol. 9, 300 (2014).34. Fischer, S., Bronstein, N. D., Swabeck, J. K., Chan, E. M. & Alivisatos, A. P. Precise Tuning of Surface Quenching for Luminescence Enhancement in Core-Shell Lanthanide-Doped Nanocrystals. Nano Lett. 16, 7241-7247 (2016).35. Johnson, N. J. J., He, S., Diao, S., Chan, E. M., Dai, H. & Almutairi, A. Direct Evidence for Coupled Surface and Concentration Quenching Dynamics in Lanthanide-Doped Nanocrystals. Journal of the American Chemical Society 139, 3275-3282 (2017).36. Liu, Q., Zhang, Y., Peng, C. S., Yang, T., Joubert, L.-M. & Chu, S.Single upconversion nanoparticle imaging at sub-10 W cm-2 irradiance. Nat.Photonics 12, 548-553 (2018).37. Chen, X., Jin, L., Kong, W., Sun, T., Zhang, W., Liu, X., Fan, J., Yu, S. F. & Wang, F. Confining energy migration in upconversion nanoparticles towards deep ultraviolet lasing. Nat. Commun. 7, 10304 (2016).38. Wang, F., Deng, R., Wang, J., Wang, Q., Han, Y., Zhu, H., Chen, X. & Liu, X. Tuning upconversion through energy migration in core-shell nanoparticles. Nat. Mater. 10, 968-973 (2011). 39. Gamelin, D. R., Luthi, S. R. & Gdel, H. U. The Role of Laser Heating in the Intrinsic Optical Bistability of Yb3+-Doped Bromide Lattices. The Journal of Physical Chemistry B 104, 11045-11057 (2000).40. Butcher, J. C. Numerical Methods for Ordinary Differential Equations. (Wiley, 2016).41. Goldner, P. & Pelle, F. Photon avalanche fluorescence and lasers. Optical Materials 5, 239-249 (1996).42. Joubert, M. F., Guy, S. & Jacquier, B. Model of the photon-avalanche effect. Phys. Rev. B 48, 10031-10037 (1993).43. Hong, G., Diao, S., Chang, J., Antaris, A. L., Chen, C., Zhang, B., Zhao, S., Atochin, D. N., Huang, P. L., Andreasson, K. I., Kuo, C. J. & Dai, H. Through-skull fluorescence imaging of the brain in a new near-infrared window. Nat. Photonics 8, 723-730 (2014).44. Ostrowski, A. D., Chan, E. M., Gargas, D. J., Katz, E. M., Han, G., Schuck, P. J., Milliron, D. J. & Cohen, B. E.Controlled Synthesis and Single-Particle Imaging of Bright, Sub-10 nm Lanthanide-Doped Upconverting Nanocrystals. ACS Nano 6, 2686-2692 (2012).45. Hossan, M. Y., Hor, A., Luu, Q., Smith, S. J., May, P. S. & Berry, M. T. Explaining the Nanoscale Effect in the Upconversion Dynamics of β-NaYF4:Yb3+, Er3+ Core nd Core-Shell Nanocrystals. The Journal of Physical Chemistry C 121, 16592-16606 (2017).46. Teitelboim, A., Tian, B., Garfield, D. J., Fernandez-Bravo, A., Gotlin, A. C., Schuck, P. J., Cohen, B. E. & Chan, E. M. Energy Transfer Networks within Upconverting Nanoparticles Are Complex Systems with Collective, Robust, and History-Dependent Dynamics. The Journal of Physical Chemistry C 123, 2678-2689 (2019).47. Chan, E. M., Gargas, D. J., Schuck, P. J. & Milliron, D. J. Concentrating and Recycling Energy in Lanthanide Codopants for Efficient and Spectrally Pure Emission: The Case of NaYF4:Er3+ / Tm3+ Upconverting Nanocrystals. The Journal of Physical Chemistry B 116, 10561-10570 (2012).48.Corle, T. R. & Kino, G., S. Confocal Scanning Optical Microscopy and Related Imaging Systems. (Academic Press, 1996).49. Chen, C., Wang, F., Wen, S., Su, Q. P., Wu, M. C. L., Liu, Y., Wang, B., Li, D., Shan, X., Kianinia, M., Aharonovich, I., Toth, M., Jackson, S. P., Xi, P. & Jin, D. Multi-photon near-infrared emission saturation nanoscopy using upconversion nanoparticles. Nat. Commun. 9, 3290 (2018).50. Pichaandi, J., Boyer, J.-C., Delaney, K. R. & van Veggel, F. C. J. M. Two-Photon Upconversion Laser (Scanning and Wide-Field) Microscopy Using Ln3+-Doped NaYF4 Upconverting Nanocrystals: A Critical Evaluation of their Performance and Potential in Bioimaging. The Journal of Physical Chemistry C 115, 19054-19064 (2011).51. Auzel, F., Chen, Y. & Meichenin, D. Room temperature photon avalanche up-conversion in Er-doped ZBLAN glass. J. Lumin. 60-61, 692-694 (1994).52. Auzel, F. & Chen, Y. Photon avalanche luminescence of Er3+ ions in LiYF4 crystal. J. Lumin. 65, 45-56 (1995). 53. Gomes, ASL, Maciel, GS, de Arajo, RE, Acioli, LH & de Arajo, CB Diode pumped avalanche upconversion in Pr3+-doped fibers. Optics Communications 103, 361-364 (1993). 54. Martn, I. R., Rodrguez, V. D., Guyot, Y., Guy, S., Boulon, G. & Joubert, M. F. Room temperature photon avalanche upconversion in Tm3+-doped fluoroindate glasses. J.Phys.: Condens. Matter 12, 1507-1516 (2000).55. Li, Y., Wang, T., Ren, W., Han, J., Yin, Z., Qiu, J., Yang, Z. & Song, Z. BiOCl:Er3+ Nanosheets with Tunable Thickness for Photon Avalanche Phosphors. ACS Applied Nano Materials 2, 7652-7660 (2019).56. Garfield, D. J., Borys, N. J., Hamed, S. M., Torquato, N. A., Tajon, C. A., Tian, B., Shevitski, B., Barnard, E. S., Suh, Y. D., Aloni, S., Neaton, J. B., Chan, E. M., Cohen, B. E. & Schuck, P. J. Enrichment of molecular antenna triplets amplifies upconverting nanoparticle emission. Nat. Photonics 12, 402-407 (2018).57. Liu, Y., Teitelboim, A., Fernandez-Bravo, A., Yao, K., Altoe, M. V. P., Aloni, S., Zhang, C., Cohen, B. E., Schuck, P. J. & Chan, E. M. Controlled Assembly of Upconverting Nanoparticles for Low-Threshold Microlasers and Their Imaging in Scattering Media.ACS Nano14, 1508–1519 (2020).58. Fernandez-Bravo , A. , Wang , D. , Barnard , ES , Teitelboim , A. , Tajon , C. , Guan , J. , Schatz , GC , Cohen , BE , Chan , EM , Schuck , PJ & Odom , TW Ultralow-threshold, continuous-wave upconverting lasing from subwavelength plasmons . Nat. Mater. 18, 1172–1176 (2019).59. Kilbane , JD , Chan , EM , Monachon , C , Borys , NJ , Levy , ES , Pickel , AD , Urban , JJ , Schuck , PJ & Dames , C. Far-field optical nanothermometry using individual sub-50 nm upconverting nanoparticles . Nanoscale 8, 11611–11616 (2016).60. Zhai , Y. , Zhou , Y. , Yang , X. , Wang , F. , Ye , W. , Zhu , X. , She , D. , Lu , W.D. & Han , S.-T. Near infrared neuromorphic computing via upconversion-mediated optogenetics. Nano Energy 67, 104262 (2020).61. Bradac , C. , Johnsson , MT , Breugel , M. v. , Baragiola , BQ , Martin , R. , Juan , ML , Brennen , GK & Volz , T. Room-temperature spontaneous superradiance from single diamond nanocrystals . Nat. Commun. 8, 1205 (2017).62. Asenjo-Garcia, A. (1999)., Kimble, H. J. & Chang, D. E. Optical waveguiding by atomic entanglement in multilevel atom arrays. Proceedings of the National Academy of Sciences 116, 25503 (2019).63. Joubert, M.-F., Guy, S., Jacquier, B. & Linares, C. The photon-avalanche effect: review, model and application. Optical Materials 4, 43-49 (1994).64. Guy, S., Joubert, M. & Jacquier, B. Photon avalanche and the mean-field approximation. Physical Review B 55, 8240 (1997). 65. Villanueva-Delgado, P., Biner, D. & Krmer, K. Judd-Ofelt analysis of β-NaGdF4: Yb3+, Tm3+ and β-NaGdF4: Er3+ single crystals. journal of luminescence 189, 84-90 (2017).66. Carnall, W., Crosswhite, H. & Crosswhite, H. M. Energy level structure and transition probabilities in the spectra of the trivalent lanthanides in LaF₃. Argonne ational ab.(ANL), rgonne, L United tates), 978).67. Armagan, G., Buoncristiani, A. & Di Bartolo, B. Excited state dynamics of thulium ions in Yttrium Aluminum Garnets. Optical Materials 1, 11-20 (1992).68. Shaw, L., Chang, R. & Djeu, N. Measurement of up-conversion energy-transfer probabilities in Ho: Y 3 Al 5 O 12 and Tm: Y 3 Al 5 O 12. Physical Review B 50, 6609 (1994).69. Basiev, T., Orlovskii, Y. V., Pukhov, K. & Auzel, F. Multiphonon relaxation of the energy of electronic excitation in optical crystals doped with rare-earth ions. Laser Physics 7, 1139-1152 (1997).70. Miyakawa, T. & Dexter, D.Phonon sidebands, multiphonon relaxation of excited states, and phonon-assisted energy transfer between ions in solids. Physical Review B1, 2961 (1970).71. Fischer, S., Bronstein, N. D., Swabeck, J. K., Chan, E. M. & Alivisatos, A. P. Precise tuning of surface quenching for luminescence enhancement in core-shell lanthanide-doped nanocrystals. Nano letters 16, 7241-7247 (2016).72. Goldner, P. & Pelle, F. Photon avalanche fluorescence and lasers. Optical Materials 5, 239-249, doi:https: / / doi.org / 10.1016 / 0925-3467(96)00003-1 (1996).73. Peterka, P., Kasik, I., Dhar, A., Dussardier, B. & Blanc, W. Theoretical modeling of fiber laser at 810 nm based on thulium-doped silica fibers with enhanced 3 H 4 level lifetime. Optics express 19, 2773-2781 (2011). 74. Auzel, F. & Pell, F. Bottleneck in multiphonon nonradiative transitions. Physical Review B 55, 11006 (1997).75. Chan, E. M. Combinatorial approaches for developing upconverting nanomaterials: high-throughput screening, modeling, and applications. Chem. Soc. Rev. 44, 1653-1679, doi:10.1039 / C4CS00205A (2015).76. Jackson, S. D. & King, T. A. Theoretical modeling of Tm-doped silica fiber lasers. Journal of lightwave technology 17, 948 (1999).77. Joubert, M.-F. Photon avalanche upconversion in rare earth laser materials. Optical Materials 11, 181-203, doi:https: / / doi.org / 10.1016 / S0925-3467(98)00043-3 (1999).78. Bednarkiewicz, A. & Strek, W. Laser-induced hot emission in Nd3+ / Yb3+: YAG nanocrystallite ceramics. Journal of Physics D: Applied Physics 35, 2503 (2002).79. Deng, H. et al. Additive-mediated splitting of lanthanide orthovanadate nanocrystals in water: morphological evolution from rods to sheaves and to spherulites. Crystal Growth and Design 8, 4432-4439 (2008).80. Deng, H., Yang, S., Xiao, S., Gong, H.-M. & Wang, Q.-Q. Controlled synthesis and upconverted avalanche luminescence of cerium (III) and neodymium (III) orthovanadate nanocrystals with high uniformity of size and shape. Journal of the American Chemical Society 130, 2032-2040 (2008).81. Si, X., Li, Z., Qu-Quan, W., Hong, D. & Shi-He, Y. Energy Transfer and Avalanche Upconversion of NdxY1 xVO4 Nanocrystals. Chinese Physics Letters 26, 124209 (2009).82. Joshi, C. & Rai, S. Structural, thermal, and optical properties of Pr3+ / Yb3+ co-doped oxyhalide tellurite glasses and its nano-crystalline parts. Solid state sciences 14, 997-1003 (2012).83. Joshi, C., Rai, R. & Rai, S. Structural, thermal, and optical properties of Er3+ / Yb3+ co-doped oxyhalide tellurite glasses, glass-ceramics and ceramics. Journal of Quantitative Spectroscopy and Radiative Transfer 113, 397-404 (2012).84. Babu, P. et al. Photon avalanche upconversion in Ho3+-Yb3+ co-doped transparent oxyfluoride glass-ceramics.Chemical Physics Letters 600, 34-37 (2014).85. Marciniak, L., Stefanski, M., Tomala, R., Hreniak, D. & Strek, W. Synthesis and up-conversion luminescence of Er3+ and Y b3+ codoped nanocrystalline tetra-(KLaP4O12) and pentaphosphates (LaP5O14). The Journal of Chemical Physics 143, 094701 (2015).86. Rathaiah, M. et al. Photon avalanche upconversion in Ho3+-doped gallium nano-garnets. Optical Materials 39, 16-20 (2015).87. Levy, E. S. et al. Energy-looping nanoparticles: harnessing excited-state absorption for deep-tissue imaging. ACS nano 10, 8423-8433 (2016).88. Dwivedi, Y., Bahadur, A. & Rai, S. Optical avalanche in Ho: Yb: Gd2O3 nanocrystals. Journal of Applied Physics 110, 043103 (2011).89. Liu, Y. et al. Amplified stimulated emission in upconversion nanoparticles for super-resolution nanoscopy. Nature 543, 229-233, doi:10.1038 / nature21366 (2017).90. Wang, F., Yang, B., Yu, Q., Liu, D. & Ma, W. Cooperative upconversion luminescence of Er3+ in Gd2O3 xSx phosphor.Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy 190, 312-317 (2018).91. Marciniak, L., Bednarkiewicz, A. & Elzbieciak, K. NIR-NIR photon avalanche based luminescent thermometry with Nd 3+ doped nanoparticles. Journal of Materials Chemistry C 6, 7568-7575 (2018).92. Bednarkiewicz, A., Chan, E. M., Kotulska, A., Marciniak, L. & Prorok, K. Photon avalanche in lanthanide doped nanoparticles for biomedical applications: super-resolution imaging. Nanoscale Horizons 4, 881-889 (2019).93. Li, Y. et al. BiOCl: Er3+ nanosheets with tunable thickness for photon avalanche phosphors. ACS Applied Nano Materials 2, 7652-7660 (2019).94. Denkova, D. et al. 3D sub-diffraction imaging in a conventional confocal configuration by exploiting super-linear emitters. Nature communications 10, 1-12 (2019). 95. Plschner, M. et al. Simultaneous super-linear excitation-emission and emission depletion allows imaging of upconversion nanoparticles with higher sub-diffraction resolution. Optics Express 28, 24308-24326 (2020).96. Liu, B. et al. Upconversion nonlinear structured illumination microscopy. Nano Letters (2020).97. Schermelleh, L. et al. Super-resolution microscopy demystified. Nature cell biology 21, 72-84 (2019).98. De Luca, G. M. et al. Re-scan confocal microscopy: scanning twice for better resolution. Biomedical optics express 4, 2644-2656 (2013).99. Juette, M. F. et al. Three-dimensional sub-100 nm resolution fluorescence microscopy of thick samples. Nature methods 5, 527-529 (2008).100. Schoen, I., Ries, J., Klotzsch, E., Ewers, H. & Vogel, V. Binding-activated localization microscopy of DNA structures. Nano letters 11, 4008-4011 (2011).101. Szczurek, A. et al. Imaging chromatin nanostructure with binding-activated localization microscopy based on DNA structure fluctuations.Nucleic acids research 45, e56-e56 (2017).102. York, A. G. et al. Instant super-resolution imaging in live cells and embryos via analog image processing. Nature methods 10, 1122-1126 (2013).103. Demmerle, J. et al. Strategic and practical guidelines for successful structured illumination microscopy. Nature protocols 12, 988-1010 (2017).104. Gustafsson, M. G. et al. Three-dimensional resolution doubling in wide-field fluorescence microscopy by structured illumination. Biophysical journal 94, 4957-4970 (2008).105. Heintzmann, R. & Huser, T. Super-Resolution Structured Illumination Microscopy. Chemical Reviews 117, 13890-13908, doi:10.1021 / acs.chemrev.7b00218 (2017).106. Sheppard, C. J., Mehta, S. B. & Heintzmann, R. Superresolution by image scanning microscopy using pixel reassignment. Optics letters 38, 2889-2892 (2013).107. Eggeling, C., Willig, K. I., Sahl, S. J. & Hell, S. W. Lens-based fluorescence nanoscopy. Quarterly reviews of biophysics 48, 178-243 (2015).108. Huff, J.The Airyscan detector from ZEISS: confocal imaging with improved signal-to-noise ratio and super-resolution. Nature methods 12, i-ii (2015).109. Korobchevskaya, K., Lagerholm, B. C., Colin-York, H. & Fritzsche, M. in Photonics. 41 (Multidisciplinary Digital Publishing Institute).110. Jungmann, R. et al. Quantitative super-resolution imaging with qPAINT. Nature methods 13, 439-442 (2016).111. Schnitzbauer, J., Strauss, M. T., Schlichthaerle, T., Schueder, F. & Jungmann, R. Super-resolution microscopy with DNA-PAINT. Nature protocols 12, 1198 (2017).112. Dertinger, T., Colyer, R., Iyer, G., Weiss, S. & Enderlein, J. Fast, background-free, 3D super-resolution optical fluctuation imaging (SOFI). Proceedings of the National Academy of Sciences 106, 22287-22292 (2009).113. Gustafsson, N. et al. Fast live-cell conventional fluorophore nanoscopy with ImageJ through super-resolution radial fluctuations. Nature communications 7, 1-9 (2016).114. Chen, B.-C. et al.Lattice light-sheet microscopy: imaging molecules to embryos at high spatiotemporal resolution. Science 346 (2014).115. Chang, J.-B. et al. Iterative expansion microscopy. Nature methods 14, 593-599 (2017).116 Chen, F., Tillberg, PW & Boyden, E.S. Expansion microscopy. Science 347, 543-548 (2015).117. Liu, W. et al. Breaking the Axial Diffraction Limit: A Guide to Axial Super-Resolution Fluorescence Microscopy. Laser & Photonics Reviews 12, 1700333 (2018). The problem to be solved

[0006] The objective of the present invention is to provide avalanche nanoparticles that cause large nonlinear optical phenomena.

[0007] Another objective of the present invention is to provide a method capable of causing the aforementioned large nonlinear optical phenomenon from avalanche nanoparticles or a method for manufacturing avalanche nanoparticles. means of solving the problem

[0008] Avalanche nanoparticle according to one aspect of the present invention comprises nanocrystals doped with at least 5 at% of thulium ions.

[0009] In a photon avalanche nanoparticle according to one embodiment of the present invention, the nanoparticle may contain only thulium.

[0010] In a photon avalanche nanoparticle according to one embodiment of the present invention, the nanoparticle may comprise a nanocrystal doped with 100 at% of thulium ions.

[0011] In a photon avalanche nanoparticle according to one embodiment of the present invention, the atomic concentration of doped thulium may be at least 8% or more.

[0012] In a photon avalanche nanoparticle according to one embodiment of the present invention, the near-infrared excitation wavelength of the nanocrystal may be 1064 nm or higher.

[0013] In a photovalley nanoparticle according to one embodiment of the present invention, the near-infrared excitation wavelength may be 1400 to 1490 nm.

[0014] In a photon avalanche nanoparticle according to one embodiment of the present invention, the nanoparticle may comprise a core-shell structure including at least one passivated shell (inert shell) surrounding the nanocrystal.

[0015] In a nanoparticle of avalanche according to one embodiment of the present invention, the thickness of the shell in the core-shell structured nanoparticle may be 0.5 to 1 times the radius of the core.

[0016] In a photovalley nanoparticle according to one embodiment of the present invention, the shell may be optically inactive.

[0017] In a photovalery nanoparticle according to one embodiment of the present invention, the nanoparticle is Yb 3+ It may not contain a sensitizer.

[0018] According to another embodiment, the present invention provides a photon avalanche nanoparticle comprising a plurality of nanocrystals having a combined size of nanocrystals of 100 nm or less in three-dimensional space.

[0019] According to another aspect, the present invention provides a method for inducing a photo-amplitude using nanoparticles comprising nanocrystals doped with at least 5 at% of thulium ions. Effects of the invention

[0020] According to one embodiment of the present invention, avalanche nanoparticles include nanocrystals doped with at least 5 at% of thulium ions, thereby significantly improving the emission efficiency of upconverted photons compared to conventional avalanche nanoparticles. Brief explanation of the drawing

[0021] FIG. 1A shows a Tm of 8 at% or more according to an embodiment of the present invention. 3+ Containing ions This is a schematic diagram illustrating a core-shell structured nanoparticle comprising a core and an inert shell surrounding the core, and a photo-chain amplification reaction in which a photo-avatar occurs inside the nanoparticle. FIG. 1B is a graph showing the emission light intensity according to the excitation light intensity for an avalanching nanoparticle (ANP) according to one embodiment of the present invention, and Fig. 1C is 4f of Tm3+ 12 A diagram plotting orbital energy levels (R1 and R2 represent the ground state excitation rate and excited state excitation rate, respectively, and W2 and W3 represent 3 F4 energy level and 3 Represents the aggregation rate after relaxation from the H4 energy level. FIG. 2A is a graph showing the emission light intensity at a wavelength of 800 nm versus the excitation light intensity for ensemble films of nanocrystals doped with 1 at%, 4 at%, and 8 at% Tm3+ according to an exemplary embodiment of the present invention, FIG. 2B shows a Tm of 8 at% according to an exemplary embodiment of the present invention. 3+This is a graph plotting the rise time of the emission light at a wavelength of 800 nm with respect to the excitation light intensity for an ANP containing, and FIG. 3A shows Tm of 8 at% according to an exemplary embodiment of the present disclosure. 3+ This doped ANP (top) having different core sizes and shell thicknesses and different Tm 3+ This is a diagram showing the emission light intensity at a wavelength of 800 nm versus the excitation light intensity at a wavelength of 1064 nm for ANP (bottom) having a doping concentration of , and FIG. 3B relates to W2 extracted from the data of FIG. 3A according to an exemplary embodiment of the present disclosure. This is a graph plotting threshold intensity, and FIG. 3C is a graph illustrating the up-conversion quantum yield according to an exemplary embodiment of the present disclosure, and FIG. 3D shows Tm at 4 at%, 8 at%, and 20 at% according to exemplary embodiments of the present disclosure. 3+ This is an exemplary graph illustrating brightness according to excitation light intensity for doped ANP, and FIGS. 4A and FIGS. 4B are, respectively, the saturation regime (9.9 kWcm²). -2 When excited by ) and the avalanche zone (PA regime: 7.1 kWcm -2 8 at% Tm when excited with ) 3+ It is an image of a single ANP containing, and FIG. 4C is an exemplary graph illustrating normalized intensity according to a line cut corresponding to the blue line indicated in FIG. 4A and FIG. 4B according to an exemplary embodiment of the present disclosure, and FIGS. 4D and FIGS. 4E are diagrams illustrating the theoretical simulation results for PASSI (photon-avalanche single-beam superresolution imaging) of FIGS. 4A and FIGS. 4B, respectively, and FIG. 4F is a graph showing the measured Full Width at the Half Maximum (FWHM) and simulated FWHM of single ANP PASSI images as a function of excitation light intensity according to an exemplary embodiment of the present disclosure, and FIG. 4G shows two Tm at 8 at% concentrations spaced 300 nm apart according to an exemplary embodiment of the present disclosure. 3+ This is an image obtained by gradually reducing the excitation light intensity from near the saturation light intensity to just before the avalanche threshold for ANP doped with [material], and Figure 4H is a diagram showing the theoretical simulation results for Figure 4G. FIG. 5 shows Tm of NaYF41-100 at% concentration according to an exemplary embodiment of the present disclosure. 3+ This is an exemplary set of transmission electron microscope images of ANP doped with, and FIG. 6 shows Tm at a concentration of NaYF41-20 at% according to an exemplary embodiment of the present disclosure. 3+ This is an exemplary set of transmission electron microscope images of ANP doped with, and FIG. 7 is an exemplary graph showing an avalanche threshold from a graph of emission light intensity according to excitation light intensity obtained for each ANP according to an exemplary embodiment of the present disclosure; FIG. 8 shows Tm at a concentration of 8 at% according to an exemplary embodiment of the present disclosure. 3+ This is a diagram showing the emission light intensity according to the excitation light intensity scan (increase and decrease) for nanocrystals doped with [material]. FIG. 9 shows 1-100 at% Tm with different core sizes and shell thicknesses. 3+ This is a graph showing the emission light intensity at 800 nm wavelength according to the excitation light intensity at 1064 nm wavelength for each doped ANP, and FIG. 10 is a diagram illustrating a scanning confocal microscopy system coupled with time-correlated single photon counting electronics according to an exemplary embodiment of the present disclosure, and FIG. 11 is an exemplary set of graphs illustrating the evolution of time-resolved photoluminescence below and above the avalanche threshold under excitation of a wavelength of 1064 nm, and FIG. 12 shows NaYF4: 8at% Tm according to one embodiment of the present invention 3+ nanocrystals obtained under different excitation light intensity conditions 3 H4- 3 This is a diagram showing the measured values ​​and Differential Rate Equation (DRE) simulation results for the time-resolved photoluminescence of the H6 transition (e.g., 800 nm). FIG. 13 shows 8 at% Tm for different excitation wavelengths in an NIR-II spectral window according to an exemplary embodiment of the present disclosure. 3+ This is an exemplary graph illustrating curves of opposite to opposite light intensity as a function of excitation light intensity on a doped nanoparticle film, and FIG. 14 is a graph set of data points fitted as sub-diffraction resolution images and Gaussian lineshapes according to an exemplary embodiment of the present disclosure, and FIG. 15A is an exemplary graph illustrating measured rise time versus seed excitation intensity according to an exemplary embodiment of the present disclosure, and FIG. 15B is an exemplary set of graphs illustrating time-resolved luminescence according to different seed and illumination excitation intensities according to an exemplary embodiment of the present disclosure, and FIG. 16A is an exemplary hexagonal excitation pattern overlapping with an ANP phantom (spiral dots) according to an exemplary embodiment of the present disclosure, and FIG. 16B is an exemplary emission image of only the excited ANP according to an exemplary embodiment of the present disclosure, and FIG. 17A is an exemplary diagram illustrating photovalence emission generation and ANP localization according to an exemplary embodiment of the present disclosure, and FIG. 17B is an exemplary hexagonal pattern that is shifted by a pattern period divided by 5 to obtain 5x5=25 frames according to an exemplary embodiment of the present disclosure; FIG. 17C is an exemplary localization image according to an exemplary embodiment of the present invention; FIG. 18 is an exemplary block diagram of a system according to specific embodiments of the present disclosure. Specific details for implementing the invention

[0022] The present invention will be described in more detail below through specific examples or embodiments, including the attached drawings. However, the following specific examples or embodiments are merely references for the detailed description of the present invention and the present invention is not limited thereto and may be implemented in various forms.

[0023] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. Terms used for illustrative purposes in the present invention are merely intended to effectively describe specific embodiments and are not intended to limit the present invention.

[0024] Additionally, the singular form used in the specification and the appended claims may be intended to include the plural form unless specifically indicated otherwise in the context.

[0025] Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0026] Additionally, % as described in this specification may mean atomic % (at%) unless otherwise noted.

[0027] Additionally, throughout the drawings, unless otherwise noted, the same reference numbers and letters are used to denote similar features, elements, components, or parts of the illustrated embodiments. Furthermore, although the present disclosure will now be described in detail with reference to the drawings, this is done in relation to exemplary embodiments and is not limited to the specific embodiments illustrated in the drawings and appended paragraphs.

[0028] Photon Avalanching (PA) can be a positive feedback system or method that is analogous to the second-order phase transition of ferromagnetic spin systems (e.g., see Reference 6), which has proven useful for modeling processes (e.g., see References 5 and 17). In lanthanide-based PA, a single ground-state absorption ("GSA") event initiates a chain reaction of excited-state absorption ("ESA") and cross-relaxation events between lanthanide ("Ln3+") ions, resulting in the emission of many upconverted photons (e.g., see Fig. 1A). The sensitivity of Ln3+ photophysics to local material properties has hindered the realization of PA in nanomaterials.

[0029] Avalanche-like behavior in previous nanoparticle designs ultimately leads to the formation of larger aggregated materials (e.g., see Reference 18), non-PA thermal mechanisms (e.g., see References 19 and 20), or a nonlinear order s in the range of 2 to 7 (e.g., s is It can be defined as, where I E This was the result of the formation of a pre-avalanche energy loop ("EL: Energy-Looping") (e.g., see References 6, 11, 13 and 21-27) having an emission intensity (e.g., see References 7, 11 and 22). Since the ability to process these colloidal nanomaterials in solution can be integrated into various device platforms, novel nanotechnologies, and unique environments (e.g., see References 23 and 28) using biocompatible surface chemical properties (e.g., see References 28-32), there remains a strong motivation to develop PA in nanoparticles.

[0030] According to one embodiment of the present invention, Tm 3+ doped The avalanche mechanism that can occur in nanoparticles or nanocrystals is shown in Figures 1A-1C.

[0031] Specifically, FIG. 1A shows a core-shell structured nanoparticle, wherein the core contains 8 at% or more of Tm 3+ Containing ions This represents an avalanching nanoparticle (ANP) in which an avalanche occurs, and Yb in the upper right corner of Fig. 1A. 3+ The Energy Transfer Upconversion (ETU) process, in which the photovalery is excluded through ground-state absorption by ions, was schematically represented and compared.

[0032] Figure 1B is a diagram showing, as an example, a model plot of Photon Avalanching Giant Nonlinear Optical Response Curve showing the three stages of the process before, during, and after the photon avalanche.

[0033] Fig. 1C shows thulium ions (Tm 3+ )'s 4f 12 This is a diagram plotting orbital energy levels, where R1 and R2 represent the ground state excitation rate and the excited state excitation rate, respectively, and W2 and W3 are, respectively 3 F4 energy level and 3It represents the aggregation rate after relaxation following the stabilization process from the H4 energy level. In this case, these light absorption and aggregation rates explain radiative and non-radiative stabilization pathways while simultaneously excluding cross-relaxation (CR) or other forms of energy transfer processes. Additionally, s 31 It can be the same as or substantially the same as the CR speed.

[0034] In one embodiment, the nanoparticles that induce avalanche may comprise nanocrystals doped with at least 4 at%, 5 at%, 6 at%, 7 at%, 8 at%, 9 at%, and 10 at% of thulium ions.

[0035] In a more specific example, the avalanche nanoparticles may comprise nanocrystals doped with thulium ions in an amount of 4 to 100 at%, 5 to 100 at%, 6 to 100 at%, 7 to 100 at%, 8 to 100 at%, 9 to 100 at%, and 10 to 100 at%, and may comprise nanocrystals doped with 100 at% of thulium ions.

[0036] As a non-limiting example, the avalanche nanoparticles may comprise nanocrystals doped with 5 to 50 at%, 5 to 40 at%, 5 to 30 at%, 6 to 30 at%, 6 to 30 at%, and 8 to 20 at% of thulium ions.

[0037] At this time, the term nanocrystal may refer to a matrix doped with thulium ions at the aforementioned atomic concentration, and the nanocrystal may be a nanocrystal of an inorganic compound. For example, thulium ions may be substituted for specific elements contained in the inorganic compound or may be doped by infiltrating defect sites of the nanocrystal.

[0038] For example, avalanche nanoparticles may contain only thulium.

[0039] As a specific example, nanoparticles are Yb 3+ It may not contain a sensitizer.

[0040] In one specific example, the photon-spot nanoparticle may be a combination of multiple nanocrystals, and the combined size of the nanocrystals in three dimensions may be 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, and substantially 5 nm or more, more substantially 10 nm or more.

[0041] Specifically, in avalanche nanoparticles, doped thulium ions undergo ground state absorption (GSA) to be excited to an intermediate excited state, and these intermediate excited thulium ions can undergo excitation state absorption (ESA) once more to be excited to a high excited state. At this time, the thulium ions excited to the high excited state transfer energy to adjacent thulium ions (cross-relaxation, CR), allowing two intermediate excited thulium ions to exist. These two intermediate excited thulium ions then undergo excitation state absorption (ESA) again to be excited to a high excited state and transfer energy to adjacent thulium ions again; this cycle is repeated, forming a chain of highly excited thulium ions. At this point, the energetically unstable highly excited thulium ions suddenly return to the ground state all at once, emitting upconversion photons.

[0042] In one embodiment, the photoconversion efficiency upconverted from the photo-valley nanoparticles may be 20% or more, 30% or more, 40% or more, or 50% or more.

[0043] The design of nanocrystals for exemplary photo-valve induction can be based on the following: 1) high Ln 3+ Recent design paradigms for upconverting nanoparticles ("UCNP: UpConverting NanoParticle") emphasizing content and energy confinement ( for example, See References 23, 29 and 33-37); 2) Its slow intermediate-state decay rate W 2 Tm having 3+ The choice of ( for example, See FIG. 1A); 3) Compositions omitting sensitizers ( for example, (See Reference 22) for example, Yb in Fig. 1A 3+ ); and 4) normal Tm 3+ Ground state pumping wavelengths ( for example, Yb 3+ 800 nm or 980 nm with sensitivity; unlike Fig. 1), selection of NIR-II excitation wavelengths optimized for resonant ESA ( for example, 1064 nm ± approx. 10% or 1450 nm ± approx. 10%; Fig. 1). ( for example, (See References 6, 11, 12, 21, and 38). Based on these design specifications, a Tm with a total diameter of 16–33 nm capable of being excited in the NIR-II region and emitted in the NIR-I region at a wavelength of 800 nm. 3+ This led to the synthesis of a doped β-NaYF4 core-shell structure. for example, References 29 and 33) (see Figures 5 and 6; and Tables 1 and 2) for example, (See Reference 22). Exemplary nanocrystals can have a combined size of about 100 nanometers or less (± about 10%) in three-dimensional space.

[0044] In one embodiment, the near-infrared excitation wavelength of a thulium ion-doped nanocrystal or a nanoparticle containing said nanocrystal may be 1000 nm or more, 1005 nm or more, 1010 nm or more, 1015 nm or more, 1020 nm or more, 1030 nm or more, 1040 nm or more, 1040 nm or more, and substantially 2000 nm or less.

[0045] As a specific example, the near-infrared excitation wavelength may be 1000 to 2000 nm, 1100 to 1900 nm, 1200 to 1800 nm, 1300 to 1600 nm, 1400 to 1500 nm, or 1400 to 1900 nm.

[0046] The wavelength emitted by the induced avalanche at this time may be 600 to 1000 nm, 700 to 900 nm, or 750 to 850 nm.

[0047] In one embodiment, the avalanche nanoparticle may comprise a core-shell structured nanoparticle by further including at least one passivated shell (inert shell) surrounding the aforementioned nanocrystal. In this case, the shell may be optically inert.

[0048] In one embodiment, the thickness of the shell in the core-shell structured nanoparticle may be 0.3 to 1, 0.4 to 1, 0.5 to 1, or 0.6 to 1 relative to the radius of the core.

[0049] As a specific example, in a core-shell structure, the diameter of the core may be 5 to 50 nm, 8 to 30 nm, 10 to 25 nm, or 10 to 20 nm.

[0050] NaYF4: 1%-100% Tm according to one embodiment in FIG. 5 3+ @ NaY 0.8 Gd 0.2Transmission electron microscope images of F4 core-shell structured nanocrystals are shown. Detailed information on the size of each nanocrystal and the content of thulium ions doped in the core is summarized in Tables 1 and 2.

[0051] Additionally, NaYF4:1%-20% Tm in Fig. 6 3+ Transmission electron microscope images of the core were taken, and it was confirmed that it has an elliptical shape.

[0052] Subsequently, three critical criteria were analyzed to determine whether PA occurs ( for example, See References 5 and 6): (i) The ratio of ESA to GSA is 10 4 (In Fig. 1C) R 2 / R 1 Powerful pump laser-induced ESA compared to GSA exceeding ) for example, (See Reference 22); (ii) a clear excitation power threshold at which a large nonlinear increase in the excited state population and emission can be observed; and (iii) a slowing of the rise-time of the excited state population at the threshold. For PA, rise-times generally exceed 100 x intermediate state lifetimes and reach up to a few seconds. for example, See Reference 6). At the same time, these criteria are existing energy transfer upconversion ( for example, It represents PAs from other nonlinear multiphoton processes including ETU (inset in Fig. 1A) and energy loops. ( for example, (See Reference 22).

[0053] Tm at 800 nm measured on nanoparticle populations drop-cast on a glass substrate 3+ Referring to the plot of emission versus 1064 nm pump intensity, Tm 3+ As the content can be increased from 1% to 4%, the degree of non-linearity s It also indicates that it increases, but s It firmly exists in the energy loop regime of ≤ 7. for example, Fig. 2A). Such Tm 3+ The chain reaction of ESA and cross-relaxation at these concentrations is rate W 2 Occurring 3 It may be too slow to compensate for radiation from the F4 intermediate state and multiphoton relaxation. However, 8% Tm 3+ In doping, the combination of cross-relaxation and ESA acts as a gain, and a non-linear gradient exceeding the maximum value of 7 observed in existing pre-photon avalanche systems s > 22 can be achieved ( for example, Fig. 2A, gray circles), approximately 20kW cm -2 A clear threshold can be observed at the pump strength ( for example, Fig. 7, Table 3). The up-and-down scan of excitation intensity does not show measurable photobleaching or hysteresis, and therefore does not show a significant contribution from the thermal avalanche caused by excitation. for example, (See Fig. 8). for example, (See Reference 39). Importantly, all three PA criteria include this 8% Tm 3+ ANPs can be satisfied at room temperature. for example, (See Fig. 2).

[0054] In one embodiment, a non-linear gradient s It can be 5 or more, 6 or more, 7 or more, 10 or more, 13 or more, 15 or more, 20 or more, or 25 or more.

[0055] As shown in FIG. 8, Tm at an 8% concentration according to one embodiment 3+ It can be seen that the emission light intensity according to the excitation light intensity scan (increase and decrease) for nanocrystals doped with [a specific element] does not exhibit hysteresis, and in this case, the emission light intensity at a wavelength of 800 nm according to the excitation light intensity may have been measured under 1064 nm excitation conditions.

[0056] FIGS. 2A and FIGS. 2B are drawings showing the emission light intensity and rise time according to the excitation light intensity for an ANP according to one embodiment, respectively.

[0057] Specifically, FIG. 2A illustrates the 800 nm emission light intensity as a function of excitation light intensity for ensemble films of nanocrystals doped with 1%, 4%, and 8% thulium ions, respectively, where the light avalanche is 8% Tm 3+ It can be seen that it is caused by ANP. At this time, it can be seen that a photo-amphibious event can be induced in both excitation light with wavelengths of 1064 nm and 1450 nm.

[0058] Fig. 2b is 8% Tm 3+ The figure plots showing the rise time according to the excitation light intensity of ANP, and it can be seen that the rise time increases significantly up to a maximum of 608 ms near the avalanche threshold.

[0059] Additionally, 8% Tm 3+ To understand why doping of causes such nonlinear emission, the PA process in ANPs was modeled using coupled nonlinear differential rate equations. for example, DREs; see Tables 4–8). ( for example, (See References 17 and 40). 8% Tm 3+ Fitting a model to experimental data on ANPs ( for example, Fig. 2A, gray dashed line) is approximately 10,000 ( for example, ESA Rate vs. GSA Rate in Table 6 R 2 / R 1 Generate a ) ratio for PA R 2 / R 1 >10 4 Meets the criteria. for example, See References 6 and 41).

[0060] To observe the characteristic slowing in the expected excited state population growth time for PA, ( for example, See references 4, 6, 17 and 42), Tm 3+ 3 Time-dependent luminescence from the H4 level ( for example, 800 nm emission) was measured (see Fig. 2B and Figs. 10–12). The rise time can be defined as the time required to reach 95% of the asymptotic value. for example, See Fig. 11). A significant delay in luminescence rise time occurs near the PA threshold intensity, up to approximately 608 ms ( 3 Reaching nearly 400 times the F4 state lifespan ( for example, Fig. 2B), further verified that the PA mechanism is dominant in these nanoparticles.

[0061] FIG. 10 is a diagram illustrating a scanning confocal microscopy system (1000) combined with a time-correlated single photon counting electronics (1010) according to one embodiment.

[0062] The aforementioned scanning confocal microscope system (1000) may include a microscope objective lens (1020), an excitation light source (1030), a sample scanning stage (1040), an optical filter comprising a shortpass (SP) filter (1050) and a longpass (LP) filter (1060), a functional generator (1070) for synchronizing optical excitation and collection, and an optical detector comprising a single photon detector (1080) connected to time-correlated single photon counting electronics (TCSPC) and a charge-coupled-device (CCD) array (1090) coupled to a spectrometer.

[0063] Figure 11 is an exemplary set of graphs illustrating the evolution of time-resolved photoluminescence below and above the avalanche threshold under excitation at a wavelength of 1064 nm. In this case, the rise time was determined by 95% of the asymptotic value.

[0064] FIG. 12 shows NaYF4: 8% Tm according to one embodiment 3+ nanocrystals obtained under different excitation light intensity conditions 3 H4- 3 This figure illustrates the measured values ​​and Differential Rate Equation (DRE) simulation results for time-resolved photoluminescence at an H6 transition (e.g., 800 nm). In this case, the blue circle represents approximately 7.0 kW cm⁻¹. -2 Under the excitation light intensity conditions, The red circle is approximately 10.5 kW cm -2 This is the result measured under the excitation light intensity conditions.

[0065] Exemplary modeling also 3 F4 and3 We can predict a PA for much longer wavelength excitations near 1450 nm that resonates with the ESA between H4 but not with the GSA. for example, (See Fig. 1C). This may be a technically attractive wavelength range as it exceeds the absorption cutoff of Si-based detectors while being easily detectable by Si, and may also be useful for deep tissue imaging, including cranial penetrating fluorescence imaging at depths greater than 2 mm in the living mouse brain ( for example, See Reference 43). Approx. 40 kW cm -2 Maximum nonlinearity using 1450 nm excitation, along with emission versus intensity curves indicating the threshold. s = 14.9( for example, (Brown stars in Fig. 2) were observed. More generally, as shown in Fig. 13, ANPs exhibit PA for wavelengths between 1400 nm and 1470 nm, with the lowest threshold occurring at 1450 nm within this range. Accordingly, the wavelengths at which avalanches are induced may be between approximately 1400 nm (± approximately 10%) and approximately 1490 nm (± approximately 10%).

[0066] Recent theories show that achieving PA with large nonlinearity involves a complex balance between various phenomena coexisting within the material. for example, See Reference 7). However, cross-relaxation rate s 31 >> W 2 In limited cases, the DRE model has a threshold value W 2 It is predicted that it can be completely determined by (see, e.g., References 5 and 17). In ANPs, s 31 is Ln 3+ While it can be controlled by concentration, W 2The non-radioactive decay component of can be dominated by losses at surfaces and interfaces. for example, (See References 29, 34, 35, 44, and 45). To determine whether the threshold value can be reduced by rebalancing these factors, surface loss and W 2 Two new 8% Tm to reduce 3+ Core / shell structures were synthesized. These designs include thicker shells and larger core sizes than the 8% ANPs in Fig. 2, for example, and serve to further reduce the surface-to-volume ratio. Due to these changes, the threshold value actually reaches 10 kW cm⁻¹ at room temperature. -2 It was confirmed that it decreased significantly to less than for example, (See Figs. 3A and 9).

[0067] For example, Tm 3+ If you increase the content, s 31 And W changes, and therefore the PA excitation threshold value may change. To study this effect, Tm is doped. 3+ Core / shell ANPs with concentrations of 20% and 100% were synthesized (e.g., 20% Tm of different sizes 3+ ANP included; Fig. 4), the threshold value is Tm 3+ It can be observed that it increases with increasing content (e.g., see Fig. 3A). This may be consistent with recent studies showing that at these pump intensities, as the Ln content increases within the nanoparticles, excited state lifetimes may decrease, and consequently, ion-ion energy transfer (ET) increases, opening many potential relaxation pathways that collectively act to decrease and refill levels (e.g., W2 may increase) (e.g., see References 29 and 46).

[0068] Exemplary models are s 31The linear dependence between the PA threshold value and W2 can be predicted by a slope that can be determined by W3 (e.g., the excited state decay rate; see Fig. 1A, e.g.) and the excited state relaxation branching ratio (see, e.g., References 5 and 17). These three exemplary different Tm 3+ The dependencies on concentrations are shown in Fig. 3B. 31 As this increases, W3 and the quarter ratio become less important, so the slope of the threshold value—W2—curve decreases slightly. The 20% and 100% Tm lie on almost the same line. 3+ The existence of data points means that Tm 3+ s until the content reaches 20% 31 This demonstrates that the relative effects of W3 and the branching ratio are dominant and can be almost ignored. This well-defined relationship between the PA threshold and W2 shown in Fig. 3B has significant implications for sensing applications, where W2 can be modulated by the environment-dependent ET on the ANP surface, and small changes in W2 (e.g., the resulting threshold) can lead to large changes in luminescence for a given pump intensity.

[0069] To evaluate the efficiency and relative brightness of ANPs, Er 3+ and Yb 3+ Ion-covalently doped UCNP 33,47 Similar to those used to reproduce experimental up-conversion quantum yields (“QY”) as well as ELNPs (e.g., see Reference 22) (see (“SI”), computational models of the kinetics of ET in Ln3+-doped nanoparticles were used. Exemplary calculations show that for fully passivated core-shell nanoparticles, the QY is 105 W cm⁻¹. -2It is shown that approximately 40% can be reached for ANPs excited beyond the threshold (see, e.g., Fig. 3C). Although the model has known limitations (particularly the absence of higher energy excited states), the calculated QYs are consistent with both previous QY calculations for ELNPs (see, e.g., Reference 22) and QY measurements of PA-induced upconversion in fibers at room temperature (see, e.g., Reference 16). In exemplary calculations, it was found that 8% Tm3+ ANPs may be somewhat more efficient than 20% Tm3+ ANPs at this pump intensity, but the brightness of the 20% Tm3+ ANPs may be higher (see, e.g., Fig. 3C). This is because brightness can be a function of QY, but it may also be the total number of emitted photons within the ANP (e.g., brightness can be defined as the product of the wavelength-dependent Tm3+ ion absorption cross-section, Tm3+ concentration, and QY). Since the extreme nonlinearity of PA emission can be a function of both intensity-dependent QY and the excited state population, the emission intensity exhibits a more nonlinear dependence on pump fluence than on QY.

[0070] A recently proposed photon-avalanche single-beam superresolution imaging method utilizing the extreme nonlinear response of PA ("PASSI: Photon-Avalanche Single-beam Superresolution Imaging") ) As described by the concept, applications for ANPs can be single-particle super-resolution imaging. for example, See Reference 7). In scanning confocal microscopy ("SCM: Scanning Confocal Microscopy"), the magnitude of the imaging point diffusion function is ( for example, Degree of nonlinearity (as in multiphoton microscopy) s It is inversely proportional to the square root of ( for example,(See Reference 7), the full width at half maximum ("FWHM") of a nonlinear emitter imaged in SCM is given as follows:

[0071]

[0072] Gaussian optical approximation ( for example, (See Reference 48) for example, Here, NA can be the numerical aperture and λ can be the wavelength). Therefore, deep subwavelength resolution can be automatically realized using ANPs during standard SCM. Such imaging may not require complex metrology, excitation beamforming or patterning, image post-processing, or alignment procedures. for example, (See Reference 7).

[0073] In one embodiment, an exemplary single ANP imaging was performed to measure an average FWHM PASSI image spot of 75 nm or less when excited at 1064 nm at the optimal pump intensity for PASSI, which corresponds to the emission intensity at the top of the steep segment of the response curve. for example, (See Reference 7). More specifically, s = 26( for example, 8% Tm from batch processing of Fig. 3A) 3+ The image of ANP shows a short-axis FWHM of 65±7 nm and a long-axis FWHM of 81±9 nm ( for example, (Figs. 4B and 14), it has an elliptical shape due to the slightly elliptical excitation spot. This spot size matches well with the PASSI simulation values. for example, (See Fig. 4E). A comparison with a diffraction-limited excitation spot size of 357 nm FWHM clearly demonstrates the advantage of the extreme nonlinearity of the PA. for example, (Refer to Fig. 4A). In Fig. 4A, the spot size can be approximately 220 nm FWHM when excited closer to the saturation regime, where the degree of nonlinearity s As expected, it could be quite low. for example, (See Reference 7). for example, (Refer to Fig. 4D). s The theoretical resolution limit considering = 26 can be 70 nm, which matches very well with the measured values. The PASSI super-resolution and its intrinsic power dependence are only resolvable when excited near saturation, but PA emission vs. The intensities in the steep region of the pump intensity curve are clearly evident through two easily resolvable ANPs separated by 300 nm. for example, (See Figs. 4G and 4H). Resolution is the slope of power-dependent emission ( for example, (Fig. 4F) This can be completely determined by the curve, which facilitates the selection of the optimal intensity for imaging for a given ANP architecture once the curve can be measured. for example, (See Reference 7). In addition to PASSI, there may also be notable advantages when combining steep nonlinear ANPs with existing super-resolution approaches. for example, See Table 11). For example, extreme nonlinearity and anti-Stokes luminescence are nonlinear structured illumination microscopy ("SIM") and near-infrared emission saturation ("NIRES") for a given photon budget for example, (See Reference 49) It can improve the achievable signal-to-noise and resolution limitations of methods such as nanoscopy. for example, See References 9 and 10). Also, applying the concept of photon localization accuracy to PASSI images that already exhibit a resolution of less than 100 nm ( for example,(See Fig. 4B) yields a localization accuracy of less than 2 nm for only 7,600 collected photons, compared to the generally achieved 10–40 nm accuracy. for example, See Reference 8). Longer rise times are scan rates ( for example, Recognizing that the process can be limited (see Reference 50), a multi-point excitation procedure (Figs. 15, 16, and 17) was performed, suggesting that possible scan speeds of about 4 seconds or less per frame can be achieved and reasonable using multi-point PASSI.

[0074] In one embodiment, the resolution in super-resolution nanoscopy imaging using photovalley nanoparticles may be 10 to 700 nm, 10 to 600 nm, 10 to 500 nm, 15 to 300 nm, 20 to 200 nm, 40 to 120 nm, 50 to 100 nm, and 60 to 80 nm.

[0075] FIGS. 15A and FIGS. 15B are graphs showing reduced rise times according to seed excitation.

[0076] Specifically, FIG. 15A is a diagram illustrating the rise time according to the seed excitation intensity, wherein the seed excitation intensity is the intensity of the threshold value (I th It is the strength normalized to ).

[0077] FIG. 15B is an exemplary graph illustrating time-resolved luminescence according to different seed and illumination excitation intensities, where the black dashed line represents the rise time of 90%.

[0078] In one specific example, when characterizing a PA system, the pump strength is a threshold value ( When the value can be increased up to twice the threshold value that can exceed the steep region of the ANP response curve, an increase of approximately 500–10,000 times in emission intensity was measured. for example, (Refer to Figs. 2A and 3A). The parameter Δ indicating these enhanced effects av = It can be defined as, which can be significantly larger than reported energy loop systems ( for example, Δ av ≤ 50; References 11 and 22), a simpler empirical method for identifying PA using a single measurable ratio Δ av Is R 2 / R 1 It can capture the complex balance between cross-relaxation and radiative versus non-radiative relaxation. for example, See Reference 7). ≥ 8% Tm reported herein 3+ All nanoparticles having a content of 20% Tm 3+ With a maximum value of approximately 10,000 achieved by ANPs, this standard ( for example, While satisfying Table 9), the boundary value of approximately 500 is 100% Tm 3+ This can be seen in ANPs, where the large increase in cross-relaxation rates is 3 This leads to a faster non-radioactive decline of H4. for example, See Reference 46).

[0079] Furthermore, abrupt nonlinear nanomaterials realizing photo-avalanches in engineered nanocrystals at room temperature via continuous wave pumping were observed. The photo-avalanche behavior is Tm 3+ It was observed in core-shell structures doped solely with ions at a doping concentration of 8% or higher, and the PA excitation threshold intensity at higher concentrations 3It can be completely determined by the F4 intermediate state lifetime. Additionally, PA can be achieved for excitation at 1400–1470 nm in addition to 1064 nm. Along with emission intensities that scale nonlinearly with pump intensity up to the 26th power, enabling SCM imaging resolution of less than 70 nm and photon localization of less than 2 nm, these results can provide new applications in local environment, optical and chemical reporting fields, as well as in super-resolution imaging.

[0080] (Example)

[0081] (Material)

[0082] Sodium trifluoroacetate (Na-TFA, 98%), sodium oleate, ammonium fluoride ("NH4F"), yttrium chloride ("YCl3", anhydrous, 99.99%), thulium chloride ("TmCl3", anhydrous, 99.9+%), gadolinium chloride ("GdCl3", anhydrous, 99.99%), yttrium trifluoroacetate (99.99+%), oleic acid ("Office Action", 90%), and 1-octadecene ("ODE", 90%) were purchased from Sigma-Aldrich.

[0083] (Synthesis of core ANPs)

[0084] Average diameters in the range of d = 10 to 18±1 nm ( for example, NaY having (see Table 1) 1-x Tm x The F4ANP core was synthesized. for example, (See Reference 44). NaY 1-x Tm x In the case of x=0.01 in the F4ANP core ( for example, 1% Tm 3+(meaning doping), YCl3 (0.99 mmol, 193.3 mg), and TmCl3 (0.01 mmol, 2.8 mg) were added to a 50 ml three-necked flask, and then 6 ml OA and 14 ml ODE were added to prepare a mixed solution. The mixed solution was stirred under vacuum and heated to 100°C for 1 hour. During this time, the mixed solution became clear. Afterward, the flask underwent three pump / purge cycles, each consisting of refilling with N2 to remove water and oxygen and immediately pumping under vacuum. Subsequently, sodium oleate (2.5 mmol, 762 mg) and NH4F (4 mmol, 148 mg) were added to the flask under an N2 stream. Next, the resealed flask was placed under vacuum at 100°C for 15 minutes, followed by three pump / purge cycles. Then, the flask was rapidly heated from 100°C to 320°C (ramp rate 25°C / min), maintained at 320°C for 40-60 minutes, and then the compressed air inside the flask was discharged to rapidly cool it to room temperature.

[0085] To separate the synthesized nanoparticles, ethanol was added to the solution, and the precipitated nanoparticles were separated by centrifugation (at 4000 rpm for 5 minutes). The separated nanoparticles were suspended in hexane and centrifuged to remove large, aggregated particles. The nanoparticles remaining in the supernatant were washed two more times by adding ethanol, and the nanoparticles re-separated by centrifugation were dissolved in hexane. The nanoparticles were stored in hexane with two drops of oleic acid to prevent aggregation.

[0086] (Shell growth)

[0087] A 0.1M stock solution containing 20% ​​GdCl3 and 80% YCl3 was prepared by adding YCl3 (2 mmol, 390.5 mg), GdCl3 (0.5 mmol, 131.8 mg), 10 ml OA, and 15 ml ODE to a 50 ml three-necked flask.

[0088] Subsequently, the stock solution was stirred and heated to 110°C for 30 minutes under vacuum. Then, N2 was filled into the flask, and it was heated to 200°C for about 1 hour until the solution became clear and no solid was observed in the flask. Afterward, the flask was cooled to 100°C and stored under vacuum for 30 minutes. For the 0.2M Na-TFA solution, Na-TFA (4 mmol, 544 mg), 10 ml OA, and 10 ml ODE were stirred in the flask under vacuum at room temperature for 2 hours until all chemicals were dissolved.

[0089] Using the Workstation for Automated Nanocrystal Discovery and Analysis (WANDA), 3-9 nm thick NaY 0.8 Gd 0.2 F4 shells (see Table 1) were grown on the ANP core using a layer-by-layer protocol. for example, (See Reference 3).

[0090] For a shell thickness of 3 nm, 6 mL of ODE and 4 mL of OA were added to the dried ANP cores and then heat-treated at 280°C at a rate of 20°C / min in a WANDA glove box. Subsequently, 0.2 M Na-TFA solution and 0.1 M stock solution were alternately sprayed onto the heat-treated ANP cores according to an automated protocol. One spray was performed every 20 minutes, for a total of 12 sprays (6 sprays for each precursor). After the final spray, each reaction was annealed at 280°C for an additional 30 minutes and then rapidly cooled by a nitrogen flow.

[0091] Core-shell structured nanoparticles were separated and purified using the same method as in the aforementioned ANP core synthesis. In this way, Tm 3+ Core-shell structured NaYF4 nanoparticles (1-100%) doped with [material] were synthesized.

[0092] (Nanoparticle Morphological Characteristics)

[0093] The morphological characteristics of the nanoparticles were analyzed using a JEOL JEM-2100F field emission transmission electron microscope ("TEM") at an acceleration voltage of 200 kV, an FEI Themis 60-300 STEM / TEM operating at 300 kV, and a Tecnai T20 S-TWIN TEM operating at 200 kV with a LaB6 filament. Size statistics for approximately 100 nanoparticles were obtained using ImageJ software, and X-ray diffraction ("XRD") measurements were performed using a Bruker D8 Discover diffractometer equipped with Cu K radiation. Average core diameters and shell sizes are summarized in Fig. 3A. It was confirmed that relatively large cores could have a shape that widens slightly in one direction (elliptical) (see Fig. 6).

[0095] (Preparation of nanocrystalline film samples)

[0096] Films were prepared by drop-casting or spin-coating 40 μL of a nanoparticle suspension (1 μM suspension in hexane) onto a coverslip. The thicknesses of the prepared films were measured using a Bruker Dimension AFM.

[0098] (Optical properties of ANP)

[0099] For single ANP imaging, a diluted dispersion of nanoparticles was applied onto a glass coverslip and then placed on an inverted confocal microscope (Nikon, Eclipse Ti-S). A 1064 nm continuous-wave diode laser (Thorlabs, FELH 750) or a Ti-sapphire pulsed laser (Coherent, Chameleon OPO Vis, 1390–1510 nm, 80 MHz) was directed toward the rear aperture of a 1.49 NA 100× immersion oil objective lens (Olympus), and 3D ( for example, Direct focus was placed on a sample on a nanoscanning piezo stage (Physik Instrumente, P-545.xR8S Plano).

[0100] For the measurements of the fabricated film samples, a 0.95 NA 100x air objective lens (Nikon) was used. The emitted light was collected again through the same objective lens filtered with 850 nm short-pass (Thorlabs, FESH 850) and 750 nm long-pass (Thorlabs, FELH 750) filters, and a spectrometer equipped with an EMCCD (Princeton Instruments, ProEM: 1600) was used. 2 It was transmitted to an eXcelon™3) or a single avalanche diode (Micro Photon Device, PDM series). For power-dependent measurements, a neutral density wheel with continuously varying density was used, synchronized with the acquisition system, and automatically rotated by an Arduino-controlled rotor. Powers were simultaneously recorded by a Thorlabs power meter using a glass coverslip to reflect approximately 10% of the incoming flux. Average excitation power densities were calculated using the measured laser power and 1 / e from the imaged laser spot. 2 It was calculated using the area.

[0101] (Time-Resolved Photoluminescence)

[0102] Each fabricated sample was excited by a diode laser modulated at frequencies of 0.5 to 5 Hz by a function generator (Stanford Research Systems DS345). Emitted light collected by a 0.95 NA 100x objective lens (Nikon) was detected by a single-photon avalanche diode (Micro Photon Device, PDM series). A time-correlated single-photon counting (TCSPC) device (Picoquant, Hydraharp 400) was used to record timing data.

[0104] (PA mechanism in ANPs)

[0105] As previously discussed, lanthanide-based PA initiates In this case, a single ground-state absorption ("GSA") event initiates a chain reaction of excited-state absorption ("ESA") and cross-relaxation events between lanthanide ("Ln3+") ions, resulting in the emission of many upconverted photons. This mechanism leads to 800 nm emission Tm through the positive feedback loop of the ESA from the intermediate state. 3+ 3 A population of excited states such as the H4 level (Fig. 1C) and its intermediate states ( 3 Amplify to F4"), then the second ground state Tm 3+ Cross-relaxation back to the same intermediate state while promoting ions ( for example, energy transfer process) causes for example, The cross-relaxation process is approximately 1200 cm -1 (It may be accompanied by the emission of phonons to compensate for the energy mismatch). This process occurs at every iteration of the loop. 3 The F4 population can be effectively doubled, and repeated looping results in non-linear amplification of the excitation state populations.

[0106] electronic 3 F2- 3 Since the absorption peak for the F4 transition can approach the 1064 nm excitation wavelength, ESA can be effective. However, 1064 nm photons are of the electron 3 H6- 3 Approximately 1200 cm for H5 transition -1 It has an energy mismatch, which reduces the GSA cross-section at the corresponding wavelength. Due to the energy mismatch, the GSA can become a phonon-assisted process in this case, making the oscillator intensity very small, approximately 10 times smaller than the excitation resonating with pure electronic ff transitions. 4 The stomach is weaker.

[0107] (Materials for achieving PA in nanoparticles)

[0108] PA was first observed at low temperatures (see, e.g., References 5-7, 18 and 51-55). However, in nanomaterials, the sensitivity of Ln3+ photophysics to local material properties can hinder the realization of PA and hinder the induction of photoamphibious avalanches at room temperature.

[0109] As mentioned in the text, PA-enabled nanocrystals were designed by combining four key innovations. The first is Ln 3+ This may be a recent design paradigm for upconversion nanoparticles ("UCNPs"), where, high Ln 3+ Content, engineered energy confinement, and reduced surface losses provide excellent efficiency and brightness. for example, (See References 23, 29, 33-37, and 56). The second feature is a particularly slow intermediate state decay rate that strongly influences PA behavior. W 2 Tm, an ion having 3+ ( for example, This means that Fig. 1A) can be selected. for example,(See References 5-7). A third important aspect utilizes the configuration strategy previously employed in energy loop nanoparticles ("ELNPs") ( for example, (See Reference 22), where, typical Yb 3+ Sensitizers can be omitted and high concentrations of Tm 3+ Ions can be doped into the β-phase NaYF4 matrix, thereby reducing GSA while Tm 3+ -Tm 3+ Improves cross-relaxation and ESA. for example, (See Fig. 1). The fourth key element, also shared with ELNPs, is the excitation wavelengths in the NIR-II transparency window ( for example, 1064 nm or 1450 nm; selecting FIG. 1), which is Tm 3+ Conventional wavelengths used to pump ( for example, 800 nm or 980 nm when combined with Yb3+ sensitivity; unlike Fig. 1), it can be optimized for resonant ESA while maintaining non-resonant GSA. for example, See References 6, 11, 12, 21, and 38).

[0110] These design criteria were based on a Tm with an overall diameter of 16–33 nm to determine whether nanocrystals enable PA to lead. 3+ Doped β-NaYF4 core / shell structures were synthesized. for example, (See References 29 and 33). As described in the synthesis and shell growth sections above, Tm in each ANP 3+ The doped core may be surrounded by an optically inert shell to minimize surface losses ( for example, (See Reference 33). for example, (See Figs. 1, 5, and 6, and Tables 1 and 2). These nanoparticles can be excited in the NIR-II region and emitted in the NIR-I region at a wavelength of 800 nm. for example,(See Reference 22). Spectral windows of both can be useful for imaging with limited photodegradation through living systems or scattering media. for example, See Reference 57). More generally, NIR operation and excellent photostability, along with the unique combination of steep nonlinearity and efficiency provided by PA, are applicable to subwavelength bioimaging ( for example, See References 7, 11, and 12), Photonics and Photodetection ( for example, See References 56-58), temperature ( for example, See References 13, 14, and 59) and pressure ( for example, (See Reference 15) Transduction, Neuromorphic Computing ( for example, Their utility can be suggested in applications of various arrays, including (see Reference 60) and quantum optics. ( for example, See References 61 and 62).

[0111] (Modeling the differential rate equations of avalanche behavior in ANPs)

[0112] Tm 3+ The modeling of the differential rate equation ("DRE") of the doping system was performed based on a 3-level system ( for example, (See Reference 1). The integrated velocity equations can be expressed as follows:

[0113]

[0114] These equations are the ground state and excited state absorption coefficients and , warrant officer Radiative and non-radiative relaxation rates and ( for example , excluding cross-relaxation), quarterly ratio , ( for example , W3 R divided by 3 Sum of radiative relaxation rates from the H4 level to the intermediate levels) and cross-relaxation rate Includes. Also, To consider the inverse process of cross-relaxation, the inverse process of cross-relaxation (e.g., 3 F4+ 3 F4→ 3 H6+ 3 H4) and up-conversion process (e.g., 3 F4+ 3 F4→ 3 H6+ 3 F4) S. Guy and F. Joubert 2 As in the model by and It can be considered by the term. Level in steady state populations of It can be derived by solving the integrated velocity equation using the Runge-Kutta 4th-order method.

[0115] Radiation relaxation rates have similar lattice phonon energies 3 β-NaGdF4:Tm that can have 3+ Crystal Judd-Ofelt parameters for, and Tm 3+ It can be calculated using reduction matrix elements for ions ( for example, Table 5) 4 Tm as a function of dopant concentration c 3+ Parameters that may be related to energy transfer between ions can be expressed, for example, as follows:

[0116]

[0117] the other side , , , , , and It can be derived by fitting the simulation results to the experimental data, as shown in Tables 4 and 5. Non-radiative relaxation silver It can be about twice that, and this 3 F4 and 3The energy gap between H6 levels (e.g., , Approximately 4300 cm -1 ) this 3 H4 and 3 The energy gap between H5 levels (e.g., , Approximately 5,700 cm -1 This seems reasonable considering the fact that it can be somewhat smaller than ). This model, 3 H4 and 3 The multiphonon relaxation rates of Ln3+ ions in LaF3 at the F4 level are different parameters 7,8 It can be calculated to be at least 4 times smaller than, and the shell thickness of sample number 5, surface quenching 9 Because it can exceed 6 nm, which was reported to be thick enough to prevent, and It was assumed that sample number 5 could be ignored.

[0118]

[0075] The result is the ratio of ESA to GSA speeds as a clear avalanche threshold 10 It shows that it can be 10667, exceeding the standard of 10000. The high contrast of the ESA speed is Tm 3+ It can be 1.83 times higher than doped silica fiber ( for example, Table 6). ( for example, (See Reference 11). This can be explained by the phonon energy difference of the host lattices along with linewidth reduction. The coefficients of energy transfer between ions are YAG 5 These measurements can be estimated to be about 10% of the values ​​in. The reductions can also be attributed to differences in phonon-assisted energy transfer depending on the host lattices as described by F. Auzel and F. Pelle. As absorption linewidths narrow, the overlap between the donor emission spectrum and the acceptor absorption spectrum decreases, thereby reducing cross-relaxation energy transfer.

[0119] (Calculation of absorption cross-sections in the here state)

[0120] Integrated absorption cross-sections across the entire ESA peak ( yes, σ INT,ESA ) is a recent review 13 It can be calculated from Judd-Ofelt theory using the methods described in. Given the excitation wavenumber ( ESA cross-sectional area in ) It can be calculated by assuming that the ESA absorption peak can have a Gaussian line contour with dispersion w2 (w = FWHM / (2√ln (2)).

[0121] (Exemplary calculation of quantum yield)

[0122]

[0077] 3 H4→ 3 H6 transition ( for example, An exemplary theoretical quantum yield ("QY") for 800 nm can be calculated using results from DRE simulations. The equation can be expressed as follows:

[0123]

[0124] ( h ν = pump photon energy)

[0125] Bulk materials other than NaYF4 caused an avalanche, suggesting that there may be an opportunity to develop a full class of PA probes for imaging and detection. This suggests that other dopants ( for example, Pr3+, Ho3+, and Er3+ can also be co-doped with Yb3+) and other crystalline host materials ( for example, (Li / K)(Y / Gd / Lu)F4, (La / Ce)(Cl / B)3, CdF2, Y2O3, YAG, YAlO3, LnVO4) or even thick glasses ( for example, It may be possible with ZBLAN). Therefore, as a distinguishing feature for PA in nanoparticles ( for example, PA pretreatment, sensitizer deficiency, and the use of surface passivation can facilitate the design of various PA wavelengths and additional biomedical and technical applications.

[0126] In general, the same factors that promote photoamphibious activity can encourage high nonlinearities, such as high ESA / GSA ratios, high cross-relaxation and energy transfer rates compared to other relaxation pathways, as well as emission branching rates. In particular, phonon energy and density of states, and consequently the crystal structure of the host, also play a role in the efficiency of phonon-assisted GSA and CR. Reducing the phonon energy of the host can proportionally increase the number of phonons utilized to bridge the energy gaps between excitation radiation and GSA transition energies, and can exponentially reduce GSA transition rates according to the energy gap law.

[0127] The exemplary approach used here can provide a method for designing a library of lanthanide-doped avalanche nanoparticles. CR rate s 31 and relaxation rate W 2 are Ln respectively 3+ It can be fine-tuned by changing the concentration and by surface passivation. For larger changes in composition, many material parameters can be interdependent, which can complicate the prediction of optimal materials for PA. The crystal structure determines both site symmetry and phonon energies. Meanwhile, changing the dopant type results in different transition energies, cross-relaxation rates, and relaxation rates. Therefore, in the future, high-throughput rate equation simulations that account for the above factors may be essential for rapidly screening many combinations of material parameters for PA behavior.

[0128] (Exemplary PASSI simulations of raster scan confocal imaging)

[0129] For simplicity, Gaussian beams were used without limitation in all simulations. The FWHM of the Gaussian spot is the pump beam It can be established as a diffraction-limiting equation for =1064 nm and microscope objective lens NA=1.49 ( for example (to match experimental parameters). The definition of the beam was described by Equation S7.

[0130]

[0131] such I G Beam is a binary image A center across a set of single or large homogeneous ANPs of 19.5 x 16 nm defined as Scanned by changing the position (0 = no particles, 1 = particles). The size of the TabNP image defined the size of the final image where each pixel corresponds to 1 nm in 2D space. I 0 was determined from the experimental "S" curves from Fig. 3.

[0132] I G If TabNP is multiplied, a new table representing the excitation strength at the NP location can be generated.

[0133]

[0135] The experimental "S"-shaped dependence between the pump and emission intensity was used in the simulation (( ), position of the Gaussian excitation beam The emission intensity at this It was calculated by summing the contribution of each non-zero pixel from these emission images at the location ( for example , Fig. 4).

[0136]

[0137] (Example multi-point here PASSI parallel imaging)

[0138] Simulations of multi-point excitation PASSI parallel imaging were performed in a very similar manner using some modifications to emulate detection combined with photon localization analysis. Simply put, a hexagonal pattern of Gaussian beams was generated. for example, (See Fig. 13). Independently, the phantom sample was designed as before by using a 2000x2000 binary blank image with '1's indicating the location of the ANPs. The helical pattern of the ANPs ( for example, Figure 13) was generated because it clearly illustrates the behavior of PASSI imaging with respect to the distance between ANPs under diffraction-limited optical resolution conditions. As before, by multiplying both the excitation pattern and the phantom table, a new image was generated in which pixel intensities represent pump intensities.

[0139] At this point, this data was processed in a manner different from raster scan imaging. 2D photodetector ( for example, The use of a 2D pixel array was assumed. Therefore, all nanoparticles excited by the local pump intensity IP became the source of a new diffraction-limited Gaussian spot, and its emission intensity I 0 was determined by the experimental "S"-shaped power dependence, and FWHM was calculated for the emission wavelength ( for example, λ=800 nm). These diffraction-limited points were accumulated on a virtual CCD imager. Due to the very steep power dependence of the ANPs, the hexagonal beam excitation pattern promoted reasonable avalanche emission only from these ANPs that coincided with the precise centers of the excitation beams ( for example, Green spots in Fig. 13A).

[0140]

[0087] Then, by adopting a photon localization method and searching for local maxima, the locations of individual ANPs can be accurately determined. Hexagonal pattern in the X and Y directions ( for example,Fig. 14A) is shifted by a value obtained by dividing the pattern period by 5, and 5x5 = 25 emission images are obtained ( for example, Fig. 14B), processed using the localization method mentioned above. Localized ANP information was accumulated from all 25 emission frames using the emission amplitudes ( for example, Fig. 14C). A simulated image of multiple ANPs using a hexagonal multi-point excitation pattern confirms the ability to distinguish ANPs at particle separation distances of about 80 nm.

[0141] (i) ANPs having nonlinear responses in other Ln-based nanomaterials and (ii) exemplary comparisons of PASSI using other super-resolution methods

[0142] The materials for the avalanche were originally new ( for example, It was developed in the context of realizing efficient lasers, and many successful demonstrations exist in the literature. These bulk material-based PA results have been reviewed elsewhere. for example, See References 1 and 2). As can be seen, ( for example, Although there may be many arguments regarding PA (since slopes can be higher than 4 and simple ESA / ETU may not be sufficient to explain the UC process), under certain conditions, for example, quasi-linear power dependence below the threshold, luminescence saturation at high pumping powers above the threshold, and very high slopes above the threshold ( for example, Since PA occurs when >10) and power-dependent slow rise times can be satisfied simultaneously, many claims in the references may not be justified.

[0143] FIG. 18 shows a block diagram of an exemplary embodiment of a system according to the present disclosure. For example, the exemplary procedures according to the present disclosure described herein include a processing array and / or a computing array ( for example,This can be performed by a computer hardware array (1805). For example, such a processing / computing array (1805) may be all or part of a computer / processor (1810) that may include, for example, one or more microprocessors, but is not limited thereto, and a medium accessible from the computer ( for example, Instructions stored in RAM, ROM, hard drive, or other storage devices can be used.

[0144] As shown in FIG. 18, for example, a computer-accessible medium (1815) ( for example, As described above in this specification, a storage device such as a hard disk, floppy disk, memory stick, CD-ROM, RAM, ROM, etc., or a set thereof may be provided ( for example, (Communicating with the processing array (1805). The computer-accessible medium (1815) may contain executable instructions (1820) thereon. Additionally or alternatively, a storage array (1825) may be provided separately from the computer-accessible medium (1815), which may provide instructions to the processing array (1805) to configure the processing array to execute certain exemplary procedures, processes, and methods, for example, as described above.

[0145] Additionally, the exemplary processing array (1805) may be provided with or include an input / output port (1835) which may include, for example, a wired network, a wireless network, the Internet, an intranet, a data collection probe, a sensor, etc. As shown in FIG. 18, the exemplary processing array (1805) may communicate with an exemplary display array (1830), which may be a touch screen configured to input information to the processing array in addition to outputting information from the processing array, for example, according to specific exemplary embodiments of the present disclosure. Additionally, the exemplary display array (1830) and / or storage array (1825) may be used to display and / or store data in a user-accessible format and / or a user-readable format.

[0146] The foregoing is merely illustrative of the principles of the present disclosure. Various modifications and changes to the described embodiments may be apparent to those skilled in the art in light of the teachings in this specification. Accordingly, it will be understood by those skilled in the art that although not explicitly shown or described in this specification, a number of systems, arrangements, and procedures may be devised that implement the principles of the present disclosure and thus fall within the spirit and scope of the present disclosure. It will be understood by those skilled in the art that various different exemplary embodiments may be used together as well as interchangeably. Furthermore, certain terms used in this disclosure, including in the specification, drawings, and claims, may be used as synonyms in certain cases, including but not limited to data and information. It will be understood that while these words and / or other words that may be synonyms with one another may be used as synonyms in this specification, there may be instances where such words are not intended to be used as synonyms. Furthermore, prior art knowledge may be explicitly incorporated herein in its entirety unless it is explicitly incorporated by reference in this specification. All referenced publications may be incorporated here in their entirety.

[0148] Table 1. Average core diameters and shell thicknesses of NaYF4: 1-100% Tm 3+ @Na0.8Gd0.2F4 Core-shell nanocrystals

[0149]

[0151] Table 2. Core sizes of nanoparticle samples with elliptical shapes.

[0153] Table 3. Threshold values ​​for avalanche induction.

[0155] Table 4. Judd-Ofelt and relaxation parameters

[0156]

[0158] Table 5. Reduced matrix element for Tm3+ (ref. 4).

[0159]

[0161] Table 6. Absorption coefficients derived from curve fitting and coefficients for energy transfer between ions

[0162]

[0164] Table 7. Phonon-assisted non-radiative relaxation rate derived from curve fitting

[0165]

[0167] Table 8. Phonon energy of the host lattice and absorption cross-section at 1064 nm.

[0168]

[0170] Table 9. Pump strength is threshold pump strength ( Increased to twice the threshold pump strength from ( Increase in emission Δav when possible

[0171]

[0173] Table 10. Exemplary comparison of representative examples of energy loop luminescence in Ln-doped nanomaterials. ITH, ISAT, SMAX, RT and τ 90 are the excitation power threshold, saturation (if provided), peak power dependency gradient, and the presence of distinct PA features—the time required to obtain approximately 90% of steady-state emission (τ). 90 Power-dependent rise times (τ) together with ) R ) ; Legend: The symbols indicate missing / unavailable information, and Symbols indicate that features have been observed but (presumably) numerical values ​​are not provided or can be extracted; NC - Nanocrystals; C@S represents core-shell NPs, where the size or composition between the core and shell may differ; To - Operating temperature; RT - Room temperature operation. I TH and I SAT Unless these figures are provided only in power units, [kW cm -2 ] could be.

[0174]

[0175]

[0177] Table 11. Overview of super-resolution microscopy techniques including PASSI.

[0178] $: Low cost, $$: Moderate cost, $$$: High cost, Possible, SR-SIM: Super-resolution structural lighting

[0179]

Claims

Claim 1 An avalanche-inducing nanoparticle comprising a nanocrystal doped with at least 5 at% of thulium ions, wherein the near-infrared excitation wavelength of the nanocrystal is 1400 to 1490 nm. Claim 2 In claim 1, the nanoparticle is an avalanche nanoparticle containing only thulium. Claim 3 In claim 1, the avalanche nanoparticle having an atomic concentration of doped thulium of at least 8%. Claim 4 delete Claim 5 delete Claim 6 Avalanche nanoparticle according to claim 1, comprising a core-shell structured nanoparticle further including at least one passivated shell (inert shell) surrounding the nanocrystal. Claim 7 In claim 6, the avalanche nanoparticle having a core-shell structure, wherein the thickness of the shell is 0.5 to 1 times the radius of the core. Claim 8 In paragraph 6, the shell is an optically inert avalanche nanoparticle. Claim 9 In claim 1, the nanoparticles are Yb 3+ Avalanche nanoparticles that do not contain a sensitizer. Claim 10 In claim 1, the avalanche nanoparticle comprises a nanocrystal doped with 100 at% thulium ions. Claim 11 An avalanche-induced nanoparticle comprising a plurality of nanocrystals having a combined size of nanocrystals of 100 nm or less in three-dimensional space, wherein the near-infrared excitation wavelength of the nanocrystals is 1400 to 1490 nm. Claim 12 delete Claim 13 delete Claim 14 In claim 11, the above-mentioned near-infrared excitation wavelength is a maximum of 1450 nm, a photonextral nanoparticle. Claim 15 In claim 11, the avalanche nanoparticle comprises a core-shell structured nanoparticle further comprising at least one passivated shell (inert shell) surrounding the nanocrystal. Claim 16 In claim 15, the thickness of the shell in the core-shell structured nanoparticle is 0.5 to 1 times the radius of the core, and the shell is an optically inert avalanche nanoparticle. Claim 17 A method for inducing a photo-amphibious induction using nanoparticles comprising nanocrystals doped with at least 5 at% of thulium ions, wherein the near-infrared excitation wavelength of the nanocrystals is 1400 to 1490 nm. Claim 18 A method for inducing a photo-amphibious avalanche according to claim 17, wherein the nanoparticles contain only thulium. Claim 19 A method for inducing an avalanche according to claim 17, wherein the atomic concentration of the doped thulium is at least 8%. Claim 20 delete Claim 21 delete Claim 22 A method for inducing a photovalery according to claim 17, comprising a core-shell structured nanoparticle further comprising at least one passivated shell (inert shell) surrounding the nanocrystal. Claim 23 A method for inducing a photo-amphibious avalanche in which, in the nanoparticle of the core-shell structure, the thickness of the shell is 0.5 to 1 times the radius of the core, and the shell is optically inert. Claim 24 In Clause 17, the above nanoparticles are Yb 3+ A method for inducing a photo-svalence that does not contain a sensitizer

Citation Information

Patent Citations

  • Reduction process of nanoparticles doped rare earth ion and nanoparticles doped reduced rare earth ion

    KR1020130093301A

  • Up and down conversion systems for improved solar cell performance or other energy conversion

    US20110126889A1